Dukungan Orang Tua Berhubungan dengan Prestasi Belajar Anak di Masa Pandemi Covid-19 - Marwan Marwan; Pariyem Pariyem; Revy Dwi Rachmadany (Universitas Malahayati Lampung, 2024)
ABSTRACT With so many people infected with Corona Virus Disease (COVID-19), the government issued a regulation on Large-Scale Social Restrictions which resulted in the teaching and learning process which is now conducted online. With these rules, parental support is needed in the child's learning process at home. Parental support is assistance given to children, especially in learning. To analyze the relationship between parental support and children's learning achievement during the COVID-19 pandemic at SDN Kartoharjo 1 Magetan. The approach used is cross sectional. The sample used by some students at SDN Kartoharjo 1 was 60 respondents, the sampling technique used cluster random sampling. From the research conducted the majority of parental support is very high with very good children's learning achievement as many as 16 respondents (26.7%). The results of the Rank Sperman test show a significant value value = 0.020 (p value = 0.020 0.05), which means that there is a relationship between parental support and learning achievement with a coefficient of r = 0.301 which indicates a sufficient relationship. H0 is rejected and H1 is accepted, meaning that there is a relationship between parental support for children's learning achievements during the COVID-19 pandemic at SDN Kartoharjo 1 Magetan. Therefore, parental support is needed to improve children's learning achievement. Keywords: Parental Support, Learning Achievement ABSTRAK Dengan banyaknnya masyarakat yang terinfeksi Corona Virus Disease COVID-19 pemerintah mengeluarkan aturan Pembatasan Sosial Berskala Besar yang berakibat pada proses belajar mengajar yang sekarang dilakukan secara online. Dengan adanya aturan tersebut dukungan orang tua diperlukan dalam proses belajar anak di rumah. Dukungan orang tua adalah bantuan yang diberikan kepada anak terutama dalam belajar. Menganalisis hubungan dukungan orang tua terhadap prestasi belajar anak di masa pandemi covid-19 di SDN Kartoharjo 1 Magetan. Pendekatan yang digunakan adalah Cross sectional. Sampel yang digunakan sebagian siswa di SDN Kartoharjo 1 sebanyak 60 responden, tehnik sampling menggunakan cluster random sampling. Dari penelitian yang dilakukan Mayoritas dukungan orang tua sangat tinggi dengan prestasi belajar anak sangat baik sebanyak 16 responden (26,7%). Hasil uji Rank Sperman menunjukkan nilai signifikan ρ value = 0,020 (p value=0,0200,05), yang berarti ada hubungan antara dukungan orang tua dengan prestasi belajar dengan nilai koefisien r = 0,301 yang menunjukkan hubungan cukup. H0 ditolak dan H1 diterima berarti ada hubungan dukungan orang tua terhadap prestasi belajar anak di masa pandemi COVID-19 di SDN Kartoharjo 1 Magetan. Oleh karena itu, dukungan orang tua sangat diperlukan untuk meningkatkan prestasi belajar anak. Kata Kunci: Dukungan Orang tua, Prestasi belajar